Professional Learning for Teachers of Nonacademic Disciplines Working in Underperforming Secondary Schools. Issue 3 (10th August 2021) - Smit, Julie; Millett, Stephanie
Abstract: This single intrinsic case study utilized complexity theory to explore a complicated narrative of in-service professional learning for teachers undergoing improvement plans in underperforming schools. This study is bounded within a master's level online graduate course. We focused on the literacy learning of one student in the course, a U.S. Army Junior Reserve Officers' Training Corps instructor who initially experienced difficulties implementing content area literacy approaches in his curriculum. These approaches were mandated by a nonprofit organization working with his school to improve test scores. The same organization also collaborated with and monitored the online graduate course to ensure that specific approaches were taught to teachers. Our goal was to use disciplinary literacy approaches to explore the unique literacy needs of subject area teachers. This study speaks to the gap between disciplinary and content area literacy approaches in in-service teacher education.